THE TEACHER'S UNDERSTANDING OF PLAYFULNESS AS A TOOL FOR LITERACY AND LITERACY - Rodrigues, Cássio Moreira; Maciel, Cilene Lima Maria Antunes (REAMEC Journal - Amazonian Network of Mathematical Education, 2023)
The objective of this work is to highlight the teacher's view regarding playfulness and pedagogical games in the classroom. This article is the result of a dissertation research. We present a clipping with partial data about interviews carried out with pedagogical teachers, working in the 3rd year of Elementary School I, in order to understand the relevance of the ludic in educational processes, in the formation of the student facing literacy and literacy in the early years. . The methodology employed has a qualitative approach of an exploratory nature, and the method used was content analysis. The instruments for data collection were carried out through semi-structured interviews with participating teachers, namely: six teaching teachers, working in the early years of Elementary School I (permanent and contracted), having as research locus two state schools in an interior municipality in the state of Mato Grosso. The results indicated, by the teachers interviewed, that playfulness is a primordial tool and that it should be applied whenever necessary in spaces destined to Elementary School I. in a positive way in the child's learning and therefore it is essential to insert it in the educational processes, mainly with regard to the process of literacy and literacy of the students.